Evaluación para la Rehabilitación del Puente de Calle Prusia - Castro-Briceño, Esteban (Instituto Tecnológico de Costa Rica, 2012)
The evaluation for the rehabilitation of the bridge at Prusia Street is essential for the community, due to its touristic and agricultural importance. It must determine the maximum load that should carry the bridge and so the solutions to rehabilitate the bridge in study, this must include the economic impact. It is also important to highlight the critical elements present on de the bridge. To realize this task, it has to be used a software for design and analysis of structures named SAP 2000, also, Excel worksheets must be done for the review of the different stresses involved in the structure. The bridge in study turns not to be as bad as the Municipality presented it, so the only non destructive test realized was the ultrasound to determinate de section of a doubtful element. Besides, the studies determinate that the bridge doesn´t comply in terms of resistance and deflection with the AASHTO normative, since in most of the load cases the stress is greater than the capability of the section. The maximum load the bridge should manage is about 18 tons, so as an immediate action, the bridge should have a cleaning and painting of the structure, and also a substitution of the deck.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción). Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2012.
Keywords: AASHTO; Bailey; Esfuerzos; Cargas